Radiographical vertical and horizontal distances influencing the presence of interproximal papilla between maxillary central incisors (Mustansiria Dental Journal, 2018)
Conventional tooth the presence of interdental papillae in the maxillary anteriorregion plays a key esthetic role. The presence or absence of the interproximal papillais of great concern to periodontists, orthodontists, restorative dentists and to patientsThe aim of the study was to determine the association between different distancesand central papilla recessionThe central papilla was visually assessed in 50 adults students of age rangedbetween (19-25 years) in dental clinic, then by using standardized periapicalradiographs for the maxillary central incisors, the following vertical distances weremeasured: papilla tip to contact point (PT-CP), bone crest to contact point (BC-CP),proximal cementoenamel junction to contact point (pCEJ-CP), bone crest to papillatip BC-PT(the papilla height (PH)).Interdental width (IDW) was measuredhorizontally. Subjects were divided into 2 groups according to interdental width(IDW) and pCEJ-CP distance respectively: 1. (28) subjects with IDW≤2mm andpCEJ–CP >4 mm as narrow-long group 2. (22) Subjects with IDW≤2mm and pCEJ–CP ≤ 4 mm as narrow-short group.Narrow-long group exhibited more papilla recession, (PT-CP) mean was 2.5mmand the difference was statistically significant. Positive correlations were foundbetween (BC-CP), (pCEJ-CP), (IDW) and central papilla recession and more strongercorrelations were found with (BC-CP) (r = 0.856). Papilla height was negativelycorrelated with (BC-CP), (pCEJ-CP), (IDW) and stronger correlation was foundbetween papilla height and (BC-CP) (r = -0.502)Central papilla recession is associated with narrow interdental width and longpCEJ-CP distance, papilla presence influenced by different distances, some of themare (BC-CP), (pCEJ-CP), (IDW) distances, (BC-CP) had stronger effect on thepresence of central papilla.